Reasons for Lack of Research In Dentistry; A Cross Sectional Survey on Dentists and Students in Teaching Hospitals of Pakistan - Shafqat Hussain; Aamna Mansur; Khuda e Dad; Farooq Taj; Ghulam Ishaq Khan; uzma khalil (Journal of Gandhara Medical and Dental Sciences, 2022)
OBJECTIVES: